Alpha-glucosidase inhibitors as potential broad based anti-viral agents - Mehta, A; Zitzmann, N; Rudd, P; Block, T; Dwek, R (Wiley, 1998)
N-Linked oligosaccharides play many roles in the fate and functions of glycoproteins. One function is to assist in the folding of proteins by mediating interactions of the lectin-like chaperone proteins calnexin and calreticulin with nascent glycoproteins. These interactions can be prevented by inhibitors of the alpha-glucosidases and this causes some proteins to be misfolded and retained within the endoplasmic reticulum. In human immunodeficiency virus (HIV) and hepatitis B virus (HBV) the misfolding of key viral envelope glycoproteins interferes with the viral life cycle. It has been demonstrated in an animal model of chronic HBV that glucosidase inhibitors can alter glycosylation and have anti-viral activity. As the mechanism of action of alpha-glucosidase inhibitors is the induction of misfolded or otherwise defective viral glycoproteins, such inhibitors may be useful therapeutics for many viruses, especially those which bud from the endoplasmic reticulum (where protein folding takes place). For example bovine viral diarrhea virus, a pestivirus akin to hepatitis C virus, is also extremely sensitive to glucosidase inhibition.